Legal Consequences for Children who are Born in Unregistered Marriage in the Perspective of Christian Laws - Ruri Setyaningsih; Tri Wahyu Anggraeni; Debora Tri Hariyadi (Faculty of Law, University of Mataram, 2020)
Aim of this study is to describe the marriage law for the Christian under marriage law and the legal consequence for the children born in a marriage that does not register as stipulated in the marriage law. Indonesia law acknowledges a marriage is legal if it conducted under the religious rules of the married couples and recorded under national law. This study aims to describe the marriage law for the Christian under marriage law and the legal consequence for the children born in a marriage that does not register as stipulated in the marriage law. Base on this study can be concluded that marriage is considered valid if it has been registered so as to have a valid legal effect, one of which the legal status of a child born of a legal marriage constitutes legal status as a legal child. While unregistered marriage resulting unrecognized legal status of the child so that child does not have legal status.